إسهامات الشعراء السعوديين في بناء الحضارة الإسلامية الحديثة: دراسة من منظور النقد الثقافي /Contributions of Saudi Poets to Building Modern Islamic Civilization: A Study from the Perspective of Cultural Criticism - Mohammed Abdullah Munwer Al Mubarak, (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2022)
ملخص البحث: يهدف هذا البحث إلى التعرُّف على إسهامات الشعراء السعوديين في غرس قيم الحضارة العربية الإسلامية المعاصرة، من خلال الرؤى التي طرحوها في شعرهم، وما بثوه فيها من قيم حضارية شاركت في بناء كيان حضاري عربي إسلامي معاصر، وقد اتخذ البحث من النصوص الشعرية " كتاب شعراء نجد المعاصرون" لعبدالله بن إدريس أنموذجاً، وما دفعني إلى اعتماد نصوص هذا الكتاب هو أنه كتاب رائد في الشعر السعودي واتجاهاته الفكرية والفنية، وقد تجاوز عدد الشعراء فيه عشرين شاعراً، ممن تنوعت نصوصهم الشعرية التي حوت تطلعاتهم للبناء الحضاري للأمة الإسلامية في العصر الحديث، كذلك لأن هؤلاء الشعراء يمثلون أبرز رواد الشعر السعودي في القرن الماضي الذين مثلوا بشعرهم المنجز الشعري السعودي الذي واكب قيام الدولة السعودية وتطورها الحضاري، كما واكب حركات التحرر والاستقلال لكثير من البلدان العربية والإسلامية الحديثة، وأن الشعراء ونصوصهم الشعرية يعدون من رواد الأدب السعوديأ أما المنهج الذي اعتمدته في البحث فقد أفدت من المنهج الثقافي النقدي الذي يهتم بالبحث عن الأنساق الثقافية في الدراسات الأدبية. وخلص البحث إلى جملة من القيم والرؤى الحياتية التي نادى بها الشعراء السعوديون لبناء مستقبل الحضارة العربية الإسلامية في العصر الحديث. الكلمات المفتاحية: إسهامات، بناء الحضارة، الشعراء السعوديون، الأمة الإسلامية. Abstract This research aims to identify the contributions of Saudi poets in inculcating the values ​​of the contemporary Arab-Islamic civilization, through the visions that they presented in their poetry, and the civilizational values ​​they spread in them that participated in building a contemporary Arab-Islamic civilized entity. The research took from the poetic texts the book “Contemporary Poets of Najd” by Abdullah bin Idris as a model. What prompted me to adopt the texts of this book is that it is a pioneering book in Saudi poetry and its intellectual and artistic trends. The number of poets in it exceeded twenty, whose poetic texts varied, which included their aspirations for the civilized building of the Islamic nation in the modern era, as well as because these poets represent the most prominent pioneers of Saudi poetry in the last century, who represented with their poetry the Saudi poetic achievement that accompanied the establishment of the Saudi state and its civilizational development, as well as the liberation and independence movements of many modern Arab and Islamic countries, and that the poets and their poetic texts are among the pioneers of Saudi literature. The research has benefited from the critical cultural approach, which is concerned with the search for cultural patterns in literary studies. The research concluded with a set of life values ​​and visions called for by Saudi poets to build the future of the Arab-Islamic civilization in the modern era. Keywords: contributions, civilization construction, Saudi poets, the Islamic nation. Abstrak Kajian ini bertujuan untuk mengenal pasti sumbangan penyair Saudi dalam menerapkan nilai-nilai tamadun Arab-Islam kontemporari, melalui visi yang mereka kemukakan dalam puisi mereka, dan nilai-nilai peradaban yang mereka sebarkan dalam diri mereka yang turut serta dalam membina peradaban Arab-Islam kontemporari. Kajian ini mengkaji teks puisi buku "Penyair-Penyair Kontemporari Najd" oleh Abdullah bin Idris sebagai model. Apa yang mendorong saya untuk menerima pakai teks buku ini ialah ia adalah buku perintis dalam puisi Saudi dan aliran intelektual dan seninya. Bilangan penyair di dalamnya melebihi dua puluh orang, yang teks puisinya berbeza-beza, termasuk aspirasi mereka untuk membina peradaban negara Islam di era moden, serta kerana penyair ini mewakili pelopor puisi Saudi yang paling terkemuka pada abad yang lalu, yang mewakili dengan puisi mereka akan pencapaian puisi Saudi yang mengiringi penubuhan negara Saudi dan perkembangan tamadunnya, serta gerakan pembebasan dan kemerdekaan banyak negara Arab dan Islam moden, dan bahawa penyair dan teks puisi mereka adalah antara pelopor kesusasteraan Saudi. Kajian ini mendapat manfaat daripada pendekatan kritik budaya, yang mementingkan pencarian corak budaya dalam kajian sastera. Kajian ini diakhiri dengan satu set nilai hidup dan visi yang disuarakan oleh penyair Saudi untuk membina masa depan tamadun Arab-Islam di era moden. Kata kunci: sumbangan, pembinaan peradaban, penyair Saudi, negara Islam.